Maternal Self-Efficacy In Stunting Prevention Among Toddlers: A Study In The Denpasar Primary Health Care Area (Study in the Denpasar Primary Health Care Work Area) - Mahendra, Ida Bagus Made Putra; Rahayu, Sri; Somoyani, Ni Ketut (Jurnal Riset Kesehatan, 2025)
According to The Indonesia Nutrition Status Survey (SSGI) in 2023, Denpasar City has the highest stunting rate among the 9 districts in Bali Province, which is almost double from the previous year (10.8%). Maternal self efficacy in preventing stunting is an important factor that need to be considered. The aim of this research was to analyze maternal self efficacy in preventing stunting in Denpasar City. The research was done in quantitative and qualitative, with a cross-sectional design. The research population consisted of mothers with toddlers aged 6-24 months in the North Denpasar Primary Health Care I, II, and III work areas. The total sample was 203 mothers of toddlers. Quantitative data were collected using questionnaires, while qualitative data were collected through in-depth interviews. The qualitative data analysis process was carried out using the manual coding method by entering the answers of each respondent, using Spearman rank and content analysis. Characteristics of mothers of toddlers: average age 31 years, number of children 2, tertiary education (49.7%), occupation as a housewife (48.8%), income above minimum wage (54.7%), permanent residence status for more than 6 months (86.7%), high self-efficacy (89.9%). The strength of the relationship is moderate with a correlation coefficient of 0.258. The results of the correlation test showed that there is a relationship between self-efficacy towards stunting prevention (p-value 0.08). Mothers who have good self-efficacy will later carry out sufficient stunting prevention. The mother's confidence in ensuring her child's growth and development according to the stages will be able to prevent stunting.